All necessary force - Brad Taylor (: Dutton, 2012)
Charged with stopping an imminent terrorist attack, the Taskforce pursues leads to Egypt, where Pike Logan and Jennifer Cahill find themselves in charge of a mission involving a weapon of unprecedented destruction.